How do the media treat the housing crisis? Inequality, ideology, and communication in comparative perspective - Díaz-Noci, Javier (Anuario ThinkEPI, 2024)
Economic inequality has multiple faces. One of them, which also has a clear impact on not only income inequality but also on wealth inequality, because it affects the ownership of goods and assets, is the housing crisis. For very different reasons, this crisis occurs in many of the capitals and cities of Europe. We have therefore compared two countries with opposite models: Ireland, one of the member states of the European Union where the population prefers to live in single-family homes, and Spain, one of the countries on the Continent where its inhabitants prefer or see themselves forced to live in apartments. For three months (from September to November 2023) we have analyzed the news about the housing crisis in the main digital media, native or not, in both countries. We have especially attended to an ideological variety in the selection of the sample, to verify, especially, the interaction between inequality of access to housing and the formation of ideological currents through Internet media.